KAJIAN MUTU IKAN TUNA (Thunnus albacares) SEGAR DI PASAR BERSEHATI MANADO - Laismina, Ade Neni; Montolalu, Lita ADY; Mentang, Feny (Sam Ratulangi University, 2014)
The purpose of this study was to determine the quality of tuna ( Thunnus albacares ) Fresh on the market Bersehati with testing TVB - N , pH , and organoleptic test by sampling time and different merchants. The method used is descriptive exploratory method , which collects data already available facts and observations in the field through pancatatan in detail and then systematically analyzed data based on quantitative and qualitative data. The results obtained by the average value of TVB-N in the Tuna (Thunnus albacares) ranged from 8.96 mg N / 100 g sample to 10.92 mg N / 100 g sample of the sampling clock 06:00 to 7:00 . The average value of TVB - N sampling clock 12:00 to 13:00 ranged between 12.16 mg N / 100 g sample to 12.88 mg N / 100 g sample . As for sampling at 16:00 to 17:00 hours ranged from 17.92 mg N / 100 g samples up to 20.72 mg N / 100 g sample. The average value of pH at 06:00 to 07:00 hours the same sample at 5.3 . Hours 12:00 to 13:00 ranged from 5.4 to 5.6 , while the hours of 16:00 to 17:00 ranged from 5.5 to 5.6. The average value of the currency organoleptic ranged from 7.6 to 7.8 on the sampling clock 6:00 a.m. to 7:00 , at 12:00 to 13:00 hours ranged from 7.0 to 7.3 , 4:00 p.m. to 17:00 hours ranged from 6.7 to 6 , 8 . The average value of organoleptic in the gills at 6:00 to 07:00 hour sampling ranged from 7.9 to 8.1, clock 12:00 to 13:00 ranged from 7.6 to 7.7 , range antara7,2 4:00p.m. to 17:00 Hours - 7.4 . The average value of the meat organoleptic sampling 6:00 to 07:00 hours ranged from 7.9 to 8.1 , 12:00 to 13:00 hours ranged from 7.5 to 7.6 , clock 16:00-17:00 ranged between 7.1 to 7 , 3 . The average value organoleptic texture sampling ranged from 6:00 to 7:00 hours to 8.0 to 8.4, 12:00 to 13:00 hours ranged from 7.2 to 7.3 , 16:00 to 17:00 hours ranged from 6.7 to 6, 8. Based on the research results of TVB-N value test, test and test the pH value value Appearance Tuna ( Thunnus albacares ) in Bersehati market is still suitable for consumption.Keywords: Tuna, Thunnus albacares, quality assessment, TVB-N, pH, appearance, freshness.